2007
DOI: 10.1002/jrs.1807
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of C6F5SO3Li in two organic solvents with different dielectric constants: a Raman spectroscopic study

Abstract: Organic solutions of lithium pentafluorobenzene sulfonate (C 6 F 5 SO 3 Li) with varying molalities in N,Ndimethyl formamide (DMF) and triethyleneglycol dimethylether (triglyme) were investigated by Raman spectroscopy. Spectral decomposition in the n s (SO 3 ) stretching region showed bands characteristic of free anions, ion pairs and various aggregates. The relative fraction of each species has been followed as a function of salt molality. In DMF, free anions dominate, while in triglyme ion pairs dominate, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that ion interactions can form either in solution or on the stationary phase, or both, and these lead to differences in surfactant concentration dependence for ionic solute retention. 1519 Vibrational spectroscopy 3336 can be employed to study ion interactions in solution to determinate the association constants, based on a shift of vibrational bands on formation of an ion complex. To test whether NBS − associates with CP + in free solution, Raman spectra of NBS − in aqueous solution were acquired as the concentration of CP + was varied.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that ion interactions can form either in solution or on the stationary phase, or both, and these lead to differences in surfactant concentration dependence for ionic solute retention. 1519 Vibrational spectroscopy 3336 can be employed to study ion interactions in solution to determinate the association constants, based on a shift of vibrational bands on formation of an ion complex. To test whether NBS − associates with CP + in free solution, Raman spectra of NBS − in aqueous solution were acquired as the concentration of CP + was varied.…”
Section: Resultsmentioning
confidence: 99%
“…These include: Raman spectra of Fe(III)-nitrilotriacetate aqueous solutions were analyzed at high concentrations close to those used in industrial processes by Loridant et al 156 ; a Raman study of the lithium coordination in 1-ethyl-3-methylimidazoliumbis(trifluoromethylsulfonyl)imide (EMI-TFSI) additive systems as lithium-ion battery ionic liquid electrolytes by Hardwick et al 157 ; a solvation structure study of magnesium, zinc, and alkaline earth metal ions in N, Ndimethylformamide, N, N-dimethylacetamide, and their mixtures studied by Raman spectroscopy and DFT calculations; ionic size and electronic effects on steric congestion by Asada et al 158 ; a line shape analyses on the C O stretching bands of acetone using a vibrational coupling model by Kobayashi and Kanesaka 159 ; a Raman and ab initio study of the conformational isomerism in the 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid by Lassègues et al 160 ; a study of the anomalous concentration dependence of the coordination behavior of Cl ion to Ln 3C ion (Ln 3C D rare-earth ion) in anhydrous LnCl 3 alcohol solutions by Yoshimura et al 161 ; experimental and computational studies of the solvation of lithium tetrafluorobrate in dimethyl sulfoxide by Xuan et al 162 ; modeling the physico-chemistry of acid sulfate waters through Raman spectroscopy of the system FeSO 4 -H 2 SO 4 -H 2 O by Sobron et al 163 ; and finally, a Raman spectroscopic study on the dissociation of C 6 F 5 SO 3 Li in two organic solvents with different dielectric constants by Hirankumar et al 164 …”
Section: Other Studies In Liquidsmentioning
confidence: 99%